The reign of relativity philosophy in physics, 1915-1925 - Ryckman, Thomas; Oxford eBooks (Oxford : Oxford University Press, 2005)
Einstein's theory of 'general relativity' (1915) was a defining event for 20th century philosophy of science. During the decisive first ten years of the theory's existence, two main ideas dominated its philosophical reception. Ryckman's book is an extended argument concerning these ideas.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Relativity (Physics) -- History; Electronic books